An analytical study of diffraction of light by a circular aperture using spherical harmonics for n≤2 (Latakia University Journal -Basic Sciences Series, 2020)
Given the importance of Spherical Harmonics and its applicability to many physical problems, in this research, the diffraction pattern of light by a circular aperture has been studied starting from Fresnel diffraction theory and the calculation of light intensity compounds  for , in addition to the calculation of light intensity along the optical axis based on spherical harmonic analysis, where the polar radius of a point on the surface of the studied circular aperture from the center of the coordinates was expressed according to the Spherical Harmonic expansion in Three-dimensional space for   . To validate this method, the light intensity obtained was compared with the previously produced axial intensity [10].